2019
DOI: 10.1186/s13293-019-0226-x
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal regulation of circuit function: sex, systems and depression

Abstract: Major depressive disorder (MDD) is a debilitating chronic illness that is two times more prevalent in women than in men. The mechanisms associated with the increased female susceptibility to depression remain poorly characterized. Aberrant neuronal oscillatory activity within the putative depression network is an emerging mechanism underlying MDD. However, innate sex differences in network activity and its contribution to depression vulnerability have not been well described. In this review, current evidence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 168 publications
(269 reference statements)
1
23
0
2
Order By: Relevance
“…As mentioned previously, the literature suggests that the HPA axis and HPG axis are closely intertwined, and in fact, it has been shown that testosterone and cortisol inhibit the release of each other [ 67 , 68 , 69 ]. If the HPG axis negatively regulates the HPA axis, then the HPG axis may play an essential role in decreasing TRD, since chronic high levels of glucocorticoids are a key contributor to the development of these disorders [ 67 , 70 ].…”
Section: Endocrinopathiesmentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned previously, the literature suggests that the HPA axis and HPG axis are closely intertwined, and in fact, it has been shown that testosterone and cortisol inhibit the release of each other [ 67 , 68 , 69 ]. If the HPG axis negatively regulates the HPA axis, then the HPG axis may play an essential role in decreasing TRD, since chronic high levels of glucocorticoids are a key contributor to the development of these disorders [ 67 , 70 ].…”
Section: Endocrinopathiesmentioning
confidence: 99%
“…Transdermal estrogen treatment has been shown to improve ratings on depression rating scales. In other studies, premenopausal females who were taking oral contraceptives (OC) were found to have decreased rates of mood disorders in the transition to menopause [ 70 ]. In another study, longer use of oral contraceptives from menarche to menopause showed a reduced risk of postmenopausal depression [ 79 ].…”
Section: Endocrinopathiesmentioning
confidence: 99%
See 1 more Smart Citation
“…We excluded women who had a physical illness that could have impaired their ability to stand the length of the interview and those whose spouses did not give permission to participate to avoid misunderstandings in the family. Pregnant women, postpartum women, and those aged 45 years and above were excluded, due to hormonal changes in these women associated with higher prevalence of depression [27]. Women above 45 years may be experiencing premenopausal or menopausal symptoms that may present as symptoms of depression hence overestimating the prevalence [28].…”
Section: Study Design and Settingmentioning
confidence: 99%
“…Bu test ile yalnızca hipokampüse değil hafızanın işlenmesine katılan diğer kortikal yapıları da (entorinal, peririnal korteks ve parahipokampal bölge) test etmiş olduk. Nesne tanıma testinin sonuçları iki yönlü ANOVA ile analiz edildiğinde l-metiyonin alan ve almayan dişi ve erkek grupları arasında anlamlı bir istatistiksel bir farklılık gözlenmemiştir (F(1,34) =2.147; p=0.1521) (Şekil 2-D).…”
unclassified